2008
DOI: 10.1086/591462
|View full text |Cite
|
Sign up to set email alerts
|

Acute Chemokine Response in the Blood and Cerebrospinal Fluid of Children with Enterovirus 71–Associated Brainstem Encephalitis

Abstract: Overexpression of the chemokine cascade in the central nervous system compartment appears to play an important role in the elicitation of the immune response to EV71. The chemokine CSF to plasma ratios suggest that IL-8, IP-10, MCP-1, and possibly MIG-but not RANTES-are synthesized in the brain in response to encephalitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
87
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 27 publications
13
87
0
Order By: Relevance
“…Elevated levels of several cytokines and chemokines have been reported for children with brainstem encephalitis and pulmonary edema (14,33,34). Likewise, the levels of proinflammatory cytokines implicated in EV71 infection, namely, IL-1␤, IL-10, MIP-2, TNF-␣, and IFN-␥, were found to be significantly elevated in infected AG129 mice.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Elevated levels of several cytokines and chemokines have been reported for children with brainstem encephalitis and pulmonary edema (14,33,34). Likewise, the levels of proinflammatory cytokines implicated in EV71 infection, namely, IL-1␤, IL-10, MIP-2, TNF-␣, and IFN-␥, were found to be significantly elevated in infected AG129 mice.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies of humans and mice have suggested the possibility of EV71-induced immunopathogenesis (8,34). Elevated levels of several cytokines and chemokines have been reported for children with brainstem encephalitis and pulmonary edema (14,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…2B). In addition, the secretion of proinflammatory cytokines following EV71 infection has been suggested to contribute to EV71 pathogenesis (3,32,37,38). We then quantified proinflammatory cytokine (TNF-␣, IL-10, MCP-1, IL-6, IFN-␥, and IL-12) levels in Flt3L-DCs from WT and TLR9KO mice infected with EV71.…”
Section: Ev71 Infection Induces Nf-b Activation Through Tlr9mentioning
confidence: 99%
“…Several studies have addressed the elevated levels of cytokines and chemokines in children with brainstem encephalitis and pulmonary edema (3,6,37). To determine whether neurological manifestations are associated with increased cytokine and chemokine levels in brain tissue, the cytokine and chemokine levels were quantified from RNA transcripts collected from infected mice at 3, 7, and 11 days p.i.…”
Section: Ev71 Infection Induces Nf-b Activation Through Tlr9mentioning
confidence: 99%
“…7,[24][25][26] In our previous study, we found that EV71 infection significantly increased the release of IL-8, IP-10, and CCL5 at 12-hour or 24-hour point of infection in human primary MDMs. 8 While Wang and others 27 explored the acute chemokine response in the blood and cerebrospinal fluid of children with EV71-associated BE and suggested that IL-8, IP-10, MCP-1, and possibly MIG, but not CCL5, were synthesized in the brain in response to encephalitis. CCL5, a chemokine produced by stimulated airway epithelial cells that attracts eosinophils, basophils, monocytes, and memory T lymphocytes, is implicated in a variety of diseases characterized by pulmonary arterial hypertension, lung eosinophilia, and inflammation.…”
Section: Resultsmentioning
confidence: 99%